THE EFFECTS OF PLANTING MEDIA AND LIQUID ORGANIC FERTILIZER TO INCREASE THE PRODUCTIVITY OF MUSTARD PLANTS IN SEMI-ARID LAND - Pareira, Magdalena Sunarty; Bria, Stefanus; Banunaek , Zofar; Naikofi, Kristina (Universitas Veteran Bangun Nusantara, 2025)
Mustard greens are an important leafy vegetable widely cultivated in North Central Timor Regency due to their high demand and their ability to grow in various soil types. Optimizing the production of this crop requires adaptive and environmentally friendly cultivation techniques. This study was conducted to assess the effects of different combinations of growing media and liquid organic fertilizer (LOF) doses on the growth and yield of mustard greens in a semi-arid region. The experiment was carried out in the greenhouse of the University of Timor from January to April 2025, and data processing was conducted at the Laboratory of the Faculty of Agriculture, Science, and Health. A factorial Completely Randomized Design (CRD) was used with two factors, namely growing media (4 levels) and LOF dosage (4 levels), resulting in 16 treatment combinations, each replicated three times, for a total of 48 experimental units. Observed parameters included vegetative growth and plant biomass. The results showed a significant interaction between the two factors on plant height, number of leaves, root volume, and fresh root weight. The best growth was obtained from the combination of soil + cattle manure with the application of 50 ml LOF. This finding indicates that the combination of solid and liquid nutrient sources can enhance fertilization efficiency and support mustard green growth under dryland conditions. Keywords: growing media, liquid organic fertilizer, semi-arid, mustard greens